Associations between sleep changes and multimorbidity patterns in middle-aged and older Chinese adults - Yin, Shuting; Zhang, Yanfang; Du, Litao; Zhou, Jianfan; Chen, Dexu (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to identify multimorbidity patterns among Chinese middle-aged and older adults and examine their associations with prior changes and long-term trajectories in sleep duration.MethodsData from 9,747 participants in the 2011 and 2020 waves of the China Health and Retirement Longitudinal Study were analyzed. Sleep duration was self-reported in 2011 and 2020 while chronic conditions were self-reported in 2020. Latent class analysis identified multimorbidity patterns. Logistic and multinomial logistic regression was used to analyze associations of sleep duration changes and trajectories with multimorbidity and multimorbidity patterns.ResultsFive multimorbidity patterns were identified: relatively healthy class (55.41%), metabolism class (23.22%), arthritis-digestive class (10.67%), respiratory class (5.42%), multi-system morbidity class (5.28%). Sleep duration decreases of ≥1.0 h were significantly associated with higher odds of overall multimorbidity and specific multimorbidity patterns, particularly metabolism, arthritis-digestive, respiratory, and multi-system morbidity classes (FDR-p < 0.05). Additionally, compared to the healthy-healthy trajectory, short-short, and healthy-short sleep trajectories were significantly associated with higher odds of multimorbidity, particularly in arthritis-digestive, respiratory, and multi-system morbidity classes, and long-short sleep trajectories were significantly associated with higher odds of multi-system morbidity classes (FDR-p < 0.05).ConclusionAmong Chinese middle-aged and older adults, prior decreases in sleep duration (≥1.0 h) and unfavorable sleep trajectories (short-short and healthy-short) were statistically associated with higher odds of overall multimorbidity and specific patterns, particularly those involving metabolic, arthritis-digestive, respiratory, and multi-system conditions.